China's Foreign-Invested Limited Partnership Enterprise An Analysis of its Legal Personality, Limited Liability and Transferable Ownership Interest /: An Analysis of its Legal Personality, Limited Liability and Transferable Ownership Interest. (2021) - Unknown
No abstract available